Expertise reversal for different forms of instructional designs in dynamic visual representations. (21st July 2014) - Khacharem, Aïmen; Zoudji, Bachir; Kalyuga, Slava
Abstract The recent advances in software and computer technology have enabled the incorporation of dynamic representations into a multitude of educational and training environments. Cognitive load theory has been extensively used to enhance learning from complex dynamic representations by providing appropriate instructional designs to manage learner cognitive load. The available evidence, however, indicates that the suggested instructional designs that are effective for novice learners can reverse and become ineffective for learners with higher levels of prior knowledge. This phenomenon is called the expertise reversal effect. This paper reviews a series of recent experimental studies that have found interactions between levels of learners' organized knowledge structures (endogenous support) and effectiveness of different instructional designs (exogenous support), leading to the expertise reversal effect. It is argued that adapting instructional designs to learners with different amount of prior knowledge is a crucial part of effective learning.